Eco-logical lives the philosophical lives of Richard Routley/Sylvan and Val Routley/Plumwood - Hyde, Dominic (White Horse Press, 2014)
Richard Sylvan and Val Plumwood were eminent twentieth-century Australian philosophers who, in the way of philosophers, devoted their lives to examining fundamental assumptions about thought and the world. They were renowned as practical and rhetorical defenders of Australia's forests, as zealous conservationists who not only campaigned for the non-human world but tried to codify philosophically an 'environmental culture' that would be ethically and rationally engaged with it. In the present volume Dominic Hyde explores their intertwined lives and complex ideas with lucidity, respect and clear-sighted affection.